IMPLIKASI PUTUSAN MAHKAMAH KONSTITUSI TERHADAP PAJAK DAERAH - Benny Gunawan Ardiansyah (JURNAL PAJAK INDONESIA, 2017)
The change in political government of Indonesian, that had taken place in the "big bang decentralization" era, create the  decentralization of power. In the fiscal decentralization, the local governments has the power to manage theirs’ finances, including tax collection. But, actually local governments can levy taxes only if there are  any assignment  from the legislators or conducted by the constitution. The extention of the local tax object produces several problems,particularly double taxation between federal and local taxes. Constitutional Court's decision for the golf tax implied the questions about the legitimacy of local taxes. Meanwhile, the construction of tax law encountered any problems, such as the legislators’ mind of state, tend to be undemocratic, tortuous and any potential overlap of double taxation in Indonesia. Perubahan politik pemerintahan Indonesia, yang terjadi pada era “big bang decentralization”, mendesak adanya desentralisasi kekuasaan. Dalam hal desentralisasi fiskal, pemerintah daerah dapat mengelola keuangannya sendiri, termasuk pemungutan pajak. Pemerintah daerah hanya dapat memungut pajak jika ada pendelegasian dari legislator nasional atau diamanatkan oleh konstitusi. Ekstensifikasi objek pajak daerah menimbulkan beberapa permasalahan, terutama ketika terjadi pajak ganda, yaitu objek pajak daerah sekaligus objek pajak pusat. Putusan MK atas pajak golf dapat berimplikasi terhadap legitimasi pajak daerah lainnya. Sementara itu, penyusunan hukum pajak menemui beberapa kendala, misalnya adanya kerancuan berpikir, cenderung tidak demokratis, berliku-liku dan terkesan tumpang tindih yang berpotensi adanya praktik pajak ganda di Indonesia.